Impaired fasting glucose, oxidative distress, and cognitive impairment. Is this the starting point on DBT cognitive decline? - Canal, María Pilar; Nini, Karen Agustina; Baez, Maria Verónica (Frontiers in Aging Neuroscience, 2022)
Different studies performed in human patients, animal models, and in vitro cell cultures, show a correlation between type 2 diabetes (DBT2) and certain neurodegenerative pathologies. Also, it was proposed that increased inflammation and- or oxidative distress are a possible cause of DBT2-accelerated cognitive decline. The onset of DBT2 is characterized by an increase in blood glucose levels due to (an inability of the body’s cells to use insulin properly) called impaired fasting glucose (IFG). Genetic and/or molecular causes of IFG have not yet been established, but metabolic syndrome, obesity, unbalanced diets, and sedentary lifestyle would be responsible, at least in part, for the multiplication in the number of this disease. It has been proposed that hyperglycemia itself causes an imbalance in the redox state and could compromise blood-brain barrier (BBB) causing neurodegeneration. For this reason, we propose, in this review, to evaluate the available data about redox state and neurocognitive studies during the IFG period.